Nitrogen fertilization drives bacterial turnover versus fungal persistence for straw-derived C and N stabilization in a wheat-maize rotation - Guocui Ren; Xiuli Xin; Haowei Ni; Xianfeng Zhang; Lan Mu; Wenliang Yang; Shuchun Ge; Shaopu Pang; Anning Zhu (Soil and Tillage Research, 2026)

A physics-guided and scene-adaptive water index for consistent surface water mapping across regions and seasons - Shanchuan Guo; Pengfei Tang; Zilong Xia; Haowei Mu; Xiaoquan Pan; Peng Zhang; Yu Chen; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A weakly supervised approach for large-scale agricultural parcel extraction from VHR imagery via foundation models and adaptive noise correction - Wenpeng Zhao; Shanchuan Guo; Xueliang Zhang; Pengfei Tang; Xiaoquan Pan; Haowei Mu; Chenghan Yang; Zilong Xia; Zheng Wang; Jun Du; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Long-term remote sensing reveals the development of informal settlements and their impact on land surface temperature in African drylands: A case study of Windhoek, Namibia - Zilong Xia; Nan Jia; Bo Yuan; Ruishan Chen; Haowei Mu; Mo Bi; Uchendu Eugene Chigbu; Penghui Jiang (Sustainable Cities and Society, 2026)

Revealing the dynamic biological flow between eastern and western China from the perspective of ecological network - Haowei Mu; Shanchuan Guo; Kaixuan Pan; Bo Yuan; Zhou Fang; Xingang Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2026)

County-level coordination between urbanization and ecological change in dryland urban agglomerations: A quantitative approach based on remote sensing - Chunqiang Li; Shanchuan Guo; Zilong Xia; Xiaoquan Pan; Haowei Mu; Hong Fang; Pengfei Tang; Peijun Du (Journal of Geographical Sciences, 2025)

Characteristics and environmental significance of sulfur isotope signatures in the water environment of typical pyrite mines - Weiqing Zhou; Peng Liu; Jianwei Zhou; Junxing Liu; Chunguang Wang; Haowei Mu; Han Jia; Jinxing Zuo (Journal of Environmental Sciences, 2025)

Quantifying the anthropogenic sensitivity of ecological patterns in arid urban agglomeration - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Chunqiang Li; Peijun Du (Applied Geography, 2025)

Moving in the landscape: Omnidirectional connectivity dynamics in China from 1985 to 2020 - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Zilong Xia; Pengfei Tang; Wei Zhang; Peng Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2025)

Quantifying the drought sensitivity of vegetation types in northern China from 1982 to 2022 - Bo Yuan; Shanchuan Guo; Xingang Zhang; Haowei Mu; Shengpeng Cao; Zilong Xia; Xiaoquan Pan; Peijun Du (Agricultural and Forest Meteorology, 2024)

Balancing photovoltaic development and cropland protection: Assessing agrivoltaic potential in China - Zilong Xia; Yingjie Li; Shanchuan Guo; Nan Jia; Xiaoquan Pan; Haowei Mu; Ruishan Chen; Meiyu Guo; Peijun Du (Sustainable Production and Consumption, 2024)

Quantifying landscape connectivity gaps between protected area and natural habitat - Haowei Mu; Shanchuan Guo; Xuecao Li; Yuyu Zhou; Yihe Lü; Xiaoping Du; Jianxi Huang; Chaode Ma; Xingang Zhang; Zilong Xia; Hong Fang; Peijun Du (Journal of Cleaner Production, 2024)

Improving food security and farmland carbon sequestration in China through enhanced rock weathering: Field evidence and potential assessment in different humid regions - Fuxing Guo; Haowei Sun; Jing Yang; Linsen Zhang; Yan Mu; Yanping Wang; Fuyong Wu (Science of The Total Environment, 2023)

Human footprints in the Global South accelerate biomass carbon loss in ecologically sensitive regions - Mengqing Geng; Xuecao Li; Haowei Mu; Guojiang Yu; Li Chai; Zhongwen Yang; Haimeng Liu; Jianxi Huang; Han Liu; Zhengshan Ju (Global Change Biology, 2023)
Human activities have placed significant pressure on the terrestrial biosphere, leading to ecosystem degradation and carbon losses. However, the full impact of these activities on terrestrial biomass carbon remains unexplored. In this study, we examined changes in global human footprint (HFP) and human‐induced aboveground biomass carbon (AGBC) losses from 2000 to 2018. Our findings show an increasing trend in HFP globally, resulting in the conversion of wilderness areas to highly modified regions. These changes have altered global biomes' habitats, particularly in tropical and subtropical regions. We also found accelerated AGBC loss driven by HFP expansion, with a total loss of 19.99 ± 0.196 PgC from 2000 to 2018, especially in tropical regions. Additionally, AGBC is more vulnerable in the Global South than in the Global North. Human activities threaten natural habitats, resulting in increasing AGBC loss even in strictly protected areas. Therefore, scientifically guided planning of future human activities is crucial to protect half of Earth through mitigation and adaptation under future risks of climate change and global urbanization.

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Experimental and numerical simulation study on mechanical properties of fiber-reinforced plastic seismic isolator - Hao Wang; Haoran Mu; Xiaoxia Guo; Yunfei Zhang; Haowei Ji; Chao Luo; Huaiping Feng; Donglin Liu (Engineering Structures, 2023)

Structure engineering of Mn2SiO4/C architecture improving the potential window boosting aqueous Li-ion storage - Xueying Dong; Yang Mu; Liuxue Shen; Haowei Wang; Chi Huang; Changgong Meng; Yifu Zhang (Chemical Engineering Journal, 2023)

Preparation and Evaluation of Novel Supersaturated Solid Dispersion of Magnolol - Jing Zhao; Pan Gao; Chengqiao Mu; Jingqi Ning; Wenbin Deng; Dongxu Ji; Haowei Sun; Xiangrong Zhang; Xinggang Yang (AAPS PharmSciTech, 2022)

Coupling relationship between construction land expansion and PM2.5 in China - Liang Zhou; Bo Yuan; Haowei Mu; Xuewei Dang; Shaohua Wang (Environmental Science and Pollution Research, 2021)